La influencia de las redes sociales en la identidad cultural contemporánea - Castillo Lascano, Hugo Ramiro (2025)
This qualitative study examines how social media impacts cultural identity in the digital age, emphasizing its role as interactive spaces that not only reflect but also transform cultural practices. Social media has created fertile ground for exploring its influence on cultural identity, especially within rural and migrant communities, where it affects self-expression and the negotiation of cultural identity. To analyze this relationship, the PRISMA method was applied, systematically reviewing academic articles published between 2019 and 2023 from established databases and conducting a bibliometric analysis to identify patterns within key topics. Findings reveal that social media fosters cultural adaptation and the formation of norms within a globalized environment, reflecting a phenomenon where youth and migrants integrate and adapt individual and collective values. These digital spaces enable experimentation and the consolidation of new cultural practices, underscoring their impact on reshaping contemporary cultural identity.